Report on the Efficient Conduct of State Enterprises - Planning Commission (Planning Commission, Government of India, 1951)
The Report on the Efficient Conduct of State Enterprises by A.D. Gorwala, commissioned by the Planning Commission of India, provides a comprehensive examination of the expanding role of the state in industrial and commercial activities and proposes structural reforms to enhance efficiency and accountability in public sector enterprises. Recognizing that state enterprises operate across diverse sectors—including public utilities, defence industries, production, and distribution—the report argues that their success must be measured not merely by profitability but by efficiency, quality of service, and timely achievement of national objectives. Gorwala critically evaluates departmental management structures and advocates for greater operational autonomy through the establishment of independent boards composed of experienced individuals from both government and industry, ensuring professional management free from excessive bureaucratic constraints. At the same time, the report underscores the importance of parliamentary oversight without political micromanagement, maintaining a balanced relationship between autonomy and accountability. Strong financial management practices, including cost accounting, statistical control, commercial auditing, consumer councils, and price tribunals, are recommended to safeguard efficiency and public interest. Emphasizing the need for skilled managerial and technical personnel, the report calls for systematic training and institutional reforms to build administrative capacity. Overall, the document presents a forward-looking framework designed to modernize governance structures in public enterprises, enabling them to function effectively within India’s broader strategy of industrialization and economic development.
Government of India Planning Commission
Keywords: State Enterprises Management; A.D. Gorwala Report; Planning Commission of India; Public Sector Governance; Autonomous Boards; Departmental vs Autonomous Management; Financial Accountability; Cost Accounting Systems; Parliamentary Oversight; Public Utilities Administration; Defence Industries Management; Public Enterprise Reform